2018
DOI: 10.1177/0300060518761304
|View full text |Cite
|
Sign up to set email alerts
|

Association of low penetrance vitamin D receptor Tru9I (rs757343) gene polymorphism with risk of premenopausal breast cancer

Abstract: ObjectiveThe aim of this study was to determine whether a novel polymorphism (Tru9I) in the low penetrance vitamin D receptor (VDR) gene is associated with risk of premenopausal breast cancer (BC).MethodsThis case-control study included 228 patients with BC and 503 healthy women living in Pakistan who were analyzed for the VDR Tru9I (rs757343) single nucleotide polymorphism. BC cases were histopathologically confirmed, and all healthy controls were age-matched with patients (age range, 20–45 years). DNA was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…The frequencies of the different SNP genotypes in our study were similar to the distributions in other studies based on people with European background for Taq1, Bsm1, and Fok1 [ 19 21 ] and based on Pakistani women for Tru91 [ 30 ]. The frequencies of the SNPs also match the 1,000 genomes European reference distribution in the National Library of Medicine [ 41 – 44 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The frequencies of the different SNP genotypes in our study were similar to the distributions in other studies based on people with European background for Taq1, Bsm1, and Fok1 [ 19 21 ] and based on Pakistani women for Tru91 [ 30 ]. The frequencies of the SNPs also match the 1,000 genomes European reference distribution in the National Library of Medicine [ 41 – 44 ].…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, the Bsm1 polymorphism has been associated with both higher and lower risk of breast cancer in a Caucasian cohort and a Hispanic cohort respectively [ 29 , 32 ]. Only one study has investigated the Tru91 polymorphism and found an association with premenopausal breast cancer in Pakistani women [ 30 ]. The Taq1 polymorphism has on the other hand been properly investigated and four studies on Caucasian and Turkish women reported no association of the polymorphism with breast cancer risk [ 19 , 21 , 28 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Very few studies have been conducted that examine the relationship between Tru9I and cancer, such as colorectal carcinoma, breast cancer, and prostate cancer. One previous study showed that genotype AA can be correlated with an increased risk of breast cancer but, however, has a negative role in prostate cancer ( Iqbal et al, 2018 ). We have hypothesized that VDR gene polymorphism may be an important factor in the risk of disease and the response to treatment in patients with HM.…”
Section: Discussionmentioning
confidence: 99%
“…You-Ling et al (2005) have not shown any association between the Tru9I polymorphism and the risk for incident sporadic colorectal adenoma. No association was observed with type 1 diabetes in the Dalmatian population (Tatijana et al, 2005) and in Caucasian populations (Balazs et al, 2002), with the nephrolithiasis in a Turkish population (Omer et al, 2016), not with the risk of premenopausal breast cancer in Pakistan (Iqbal et al, 2018).…”
Section: Discussionmentioning
confidence: 99%